ADF1 and BEAF-32 chromatin proteins affect nucleosome positioning and DNA decompaction in 61C7/C8 interband region of Drosophila melanogaster polytene chromosomes - M. B. Schwartz (Berkaeva); T. E. Pankova; S. A. Demakov (Вавиловский журнал генетики и селекции)
The formation of interphase chromosomes is a multi-level process in which DNA is compacted several thousandfold by association with histones and non-histone proteins. The first step of compaction includes the formation of nucleosomes – the basic repeating units of chromatin. Further packaging occurs due to DNA binding to histone H1 and non-histone proteins involved in enhancer-promoter and insulator interactions. Under these conditions, the genome retains its functionality due to the dynamic and uneven DNA compaction along the chromatin fiber. Since the DNA compaction level affects the transcription activity of a certain genomic region, it is important to understand the interplay between the factors acting at different levels of the packaging process. Drosophila polytene chromosomes are an excellent model system for studying the molecular mechanisms that determine DNA compaction degree. The unevenness of DNA packaging along the chromatin fiber is easily observed along these chromosomes due to their large size and specific banding pattern. The purpose of this study was to figure out the role of two non-histone regulatory proteins, ADF1 and BEAF-32, in the DNA packaging process from nucleosome positioning to the establishment of the final chromosome structure. We studied the impact of mutations that affect ADF1 and BEAF-32 binding sites on the formation of 61C7/C8 interband – one of the decompacted regions of Drosophila polytene chromosomes. We show that such mutations led to the collapse of an interband, which was accompanied with increased nucleosome stability. We also find that ADF1 and BEAF-32 binding sites are essential for the rescue of lethality caused by the null allele of bantam microRNA gene located in the region 61C7/C8.